Drug resistance patterns and genotype associations of Trichomonas gallinae in meat pigeons (Columba livia): insights from Guangdong Province, China - Cai, Haiming; Liu, Yu; Zhu, Yibin; Fang, Siyun; Wang, Dingai; Yan, Zhuanqiang; Shen, Hanqin; Liao, Shenquan; Qi, Nanshan; Li, Juan; Lin, Xuhui; Hu, Junjing; et al. (Frontiers in Veterinary Science, 2024)
Avian trichomoniasis, caused by the protozoan parasite Trichomonas gallinae, is a prevalent and economically significant disease in pigeons. This study investigated the drug resistance of T. gallinae isolates in Guangdong Province, China. The results revealed that 25.3% (20/79) of the isolates were resistant to one or more of the four nitroimidazole drugs tested, namely, metronidazole, dimetridazole, secnidazole, and tinidazole. Secnidazole elicited the highest resistance rate (19.0%; 15/79), followed by tinidazole (17.7%; 14/79), metronidazole (17.7%; 14/79), and dimetridazole (13.9%; 11/79). An enormous majority of the resistant isolates (70.0%; 14/20) exhibited resistance to multiple drugs. Additionally, the resistance rate was significantly higher in isolates from birds aged < 30 days (53.3%; 8/15) than in those from older birds (23.1%; 12/52).Moreover, no drug resistance was detected in female pigeons. The genotype of the isolated strain was also associated with drug resistance. Specifically, 50.0% (15/30) of ITS-B genotypes exhibited resistance to drugs, while only 10.2% (5/49) of ITS-A genotypes demonstrated resistance. This study also found the growth characteristics of different Trichomonas isolates to be influenced by their genotypes and initial inoculum concentrations. These findings underscore the urgent need for effective measures to control and prevent drug-resistant T. gallinae infections in pigeons, thus ensuring the stable development of the pigeon industry.